(Table T1) DOC of interstitial waters from seven ODP Leg 201 sites - David Charles Smith (PANGAEA, 2005)
This report contains dissolved organic carbon (DOC) concentration data from interstitial waters collected at three open-ocean sites (1225, 1226, and 1231) and four sites cored along the Peru margin (1227, 1228, 1229, and 1230) during Ocean Drilling Program Leg 201. The sites were selected to represent a wide range of habitats for subsurface life based on organic carbon input to the sediments. Subsurface maxima of DOC at the ocean-margin sites is consistent with in situ production of DOC through active hydrolysis of particulate organic carbon. These downhole profiles agree well with the dissolved inorganic carbon (DIC) concentrations indicating complete remineralization of some fraction DOC to DIC. The open-ocean sites exhibit relatively flat downhole profiles, indicating that diagenesis is occurring at a much lower rate at these sites.
Supplement to: Smith, DC (2005): Data report: Dissolved organic carbon in interstitial waters, equatorial Pacific and Peru margin, ODP Leg 201. In: Jørgensen, BB; D extquotesingleHondt, SL; Miller, DJ (eds.) Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 201, 1-10, https://doi.org/10.2973/odp.proc.sr.201.111.2005